Thresholds of impaired cerebral hemodynamics that predict short-term cognitive decline in asymptomatic carotid stenosis. Issue 10 (October 2016) - Buratti, Laura; Viticchi, Giovanna; Falsetti, Lorenzo; Balucani, Clotilde; Altamura, Claudia; Petrelli, Cristina; Provinciali, Leandro; Vernieri, Fabrizio; Silvestrini, Mauro
Subjects with asymptomatic carotid stenosis (ACS) may be at risk of cognitive impairment due to cerebral hypoperfusion. In this study, we aimed to detect a threshold of cerebral hemodynamics which is able to identify subjects at risk of cognitive deterioration. In subjects with ACS, cerebral vasomotor reactivity (CVR) was assessed with the breath-holding index (BHI) transcranial Doppler-based method. Cognitive deterioration was defined as a decrease in the MMSE score by ≥2 points after one year. In order to define the threshold of impaired BHI, a ROC curve analysis was performed adopting the binary difference of MMSE score as the outcome and continuous BHI as the testing variable. A total of 548 subjects completed the follow-up. Cognitive deterioration was observed in 119 patients (21.7%). The BHI value ipsilateral to the stenosis was the strongest predictor of cognitive deterioration among the variables tested. The best cut-point to discriminate between normal and abnormal BHI resulted ≤0.89. The post-test probability of cognitive deterioration for an abnormal BHI was 44%, while a normal BHI showed a post-test probability of 9% for the same outcome. The present investigation provides a threshold of reduced CVR that can be useful to identify subjects with ACS at risk of cognitive deterioration.